International Spillover Effects of Sectoral Tax Differentiation in Unionized Economies - Bertil Holmlund; Ann-Sofie Kolm (Center for Economic Studies and ifo Institute (CESifo), 2000)
The European Union has recently proposed sectoral tax differentiation as a policy to fight unemployment. The member countries are allowed to reduce the VAT rates on goods and services that are particularly labor intensive and price elastic. The paper provides a theoretical analysis of the effects of such tax reforms, with particular emphasis on the international repercussions of the policies. To that end we develop a two-country and two-sector model with monopolistic competition in the goods market and wage bargaining in the labor market. Policy externalities operate through the endogenously determined terms of trade. We examine how national and supranational commodity tax policies affect sectoral and total employment and characterize optimal commodity taxes with and without international policy cooperation. Some rough estimates of the welfare gains from policy coordination are also presented, using a calibrated version of the model.
Keywords: 330; Economic integration; imperfect competition; wage determination; policy cooperation